Implementasi Metode Takrir pada Program Tahfidz di SD Negeri 15 Kinali - Putri, Nabila Eka; Alfurqan, Alfurqan (Lembaga Yasin AlSys, 2023)
This study aims to determine the implementation of the takrir method in the Quran tahfidz program at SDN 15 Kinali, starting from planning, implementation, and evaluation. This research includes qualitative research with a descriptive approach. Data collection techniques used are observation, interviews, and documentation. The results showed that the implementation of the takrir method in the Quran tahfidz program at SDN 15 Kinali began with a plan that was held together with the school principal, PAI teachers, and the teacher council. The implementation of the takrir method in the tahfidz program is based on the syntax of the takrir method itself and the form of implementation of the takrir method at SDN 15 Kinali, namely self-takrir and shared takrir. While the form of evaluation is an oral evaluation by listening and playing rote to the teacher. The results of this study can be used as initial data for future researchers to examine this issue in different contexts and issues.